Human Capital Flows and Regional Knowledge Assets:A Simultaneous Equation Model - Alessandra Faggian; Philip McCann (European Regional Science Association (ERSA), 2004)
Our paper constructs a simultaneous equation model in order to investigate the relationship between interregional human capital knowledge flows and regional knowledge assets. In particular, with the aid of a GIS system, we model the simultaneous relationship between the interregional migration behaviour of UK students and graduates to and from university, the knowledge assets of the regions, and the regions of employment of the graduates. Our results indicate that the innovativeness of a region encourages university graduates to seek employment in that region. However, there is little or no evidence in favour of direct spillovers between university research and regional innovation. Rather, the primary role of universities appears to be as a conduit for bringing potential high quality undergraduate human capital into a region. Many of these migrants will remain in the university region for employment after graduation, thereby subsequently contributing to the innovative performance of the region. We argue therefore that the spillovers of embodied human capital appear far more important than informal spillovers between universities and local firms.
Keywords: 330